REINTERPRETING MUHAMMAD ABU ZAHRAH’S THOUGHT IN THE CONTEXT OF CONTEMPORARY ISLAMIC LAW - Hendriyanto, Hendriyanto; Nurjanah, Siti; Zulaikha, Siti; Hermanto, Agus (Law Faculty of Universitas Bandar Lampung, 2025)
This study examines two central themes in Muhammad Abu Zahrah’s thought: the key concepts of ijtihad, maqashid al-shariah, and justice in Islamic law, and their application in contemporary contexts. These concepts underpin his legal philosophy and are particularly relevant in addressing current legal challenges, such as women's rights in inheritance. The main objective is to analyze the relevance and application of Abu Zahrah’s ideas in modern Islamic legal systems. Using a descriptive qualitative approach, the study draws on primary sources from Abu Zahrah’s writings and secondary data from current literature and scholarly journals. Data collection methods include literature review, content analysis, and comparative studies with other Islamic legal thinkers. Abu Zahrah advocates for dynamic ijtihad to address contemporary issues not explicitly regulated in classical texts, asserting that Islamic law must be adaptive and socially responsive. His ideas offer an alternative to rigid interpretations, especially in areas like family law and human rights. The study finds that Abu Zahrah’s thought provides a strong framework for developing more just, relevant, and context-sensitive Islamic legal systems in the face of globalization and legal dualism in many Muslim countries.